The viability and acceptability of a Virtual Wound Care Command Centre in Australia. Issue 7 (24th May 2022) - Barakat‐Johnson, Michelle; Kita, Badia; Jones, Aaron; Burger, Mitchell; Airey, David; Stephenson, John; Leong, Thomas; Pinkova, Jana; Frank, Georgina; Ko, Natalie; Kirk, Andrea; Frotjold, Astrid; et al.
Abstract: The objective of this study was to assess the viability and acceptability of an innovative Virtual Wound Care Command Centre where patients in the community, and their treating clinicians, have access to an expert wound specialist service that comprises a digitally enabled application for wound analysis, decision‐making, remote consultation, and monitoring. Fifty‐one patients with chronic wounds from 9 centres, encompassing hospital services, outpatient clinics, and community nurses in one metropolitan and rural state in Australia, were enrolled and a total of 61 wounds were analysed over 7 months. Patients received, on average, an occasion of service every 4.4 days, with direct queries responded to in a median time of 1.5 hours. During the study period, 26 (42.6%) wounds were healed, with a median time to healing of 66 (95% CI: 56‐88) days. All patients reported high satisfaction with their wound care, 86.4% of patients recommended the Virtual Wound Care Command Centre with 84.1% of patients reporting the digital wound application as easy to use. Potential mean travel savings of 99.65 for rural patients per visit were recognised. The data revealed that the Virtual Wound Care Command Centre was a viable and acceptable patient‐centred expert wound consultation service for chronic wound patients in the community.